On the reliability of absolute palaeointensity determinations on basaltic rocks bearing a thermochemical remanence - raw data for figures 5-10 - Valeriy Shcherbakov; Sergey Gribov; Florian Lhuillier; Natalia Aphinogenova; Vladimir Tsel extquotesinglemovich (PANGAEA, 2019)
We investigated the acquisition of thermochemical remanent magnetization (TCRM) on basaltic rocks from the volcanic island of São Tomé (Gulf of Guinea) and from the southern part of the Red Sea Rift, both containing homogeneous titanomagnetite grains with Curie temperatures of 100-200 °C. The TCRM was created in a rotating thermomagnetometer by cooling the samples from 570 to 200 °C at a rate of 1 °C per hour in the presence of a laboratory magnetic field of 50 μT. The TCRM acquisition occurred at high temperature T > 520 °C through the nucleation of ilmenite lamellae dividing the titanium-magnetite cells. Mutual Fe-Ti diffusion moved the composition of the cells closer to that of magnetite, leading to an increase in the Curie temperature T. The TCRM was formed at practically fixed volume of the titanomagnetite cells when T exceeded T. The Thellier-style experiments conducted on the samples bearing a laboratory induced TCRM, revealed palaeointensity estimates within 5% to expected value. This conclusion radically differs from previous results obtained in the case of a pure chemical remanent magnetization, and gives hope that a TCRM could be a robust source of palaeomagnetic information, yielding unbiased palaeointensity determinations.